Transformasi sosial dalam magnum opus Borneo: teks dan konteks - Awang Azman Awang Pawi, (Universiti Kebangsaan Malaysia, 2010)
The idea of social transformation is not something new in the island of Borneo-Kalimantan. It has been discussed since over 100 years ago. Thus, this paper will analyze the initial idea of social transformation in developing the society based on the texts and contexts of Sarawakian Malay authors who are regarded as not only the earliest in Borneo-Kalimantan but in South East Asia as well. This paper proves that the idea of social transformation should not be viewed in a narrow political party context, but from the aspect of development in developing the nation in a wider perspective in line with the zeitgeist in understanding the authors’ weltanschauung. The first novel, Hikayat Panglima Nikosa, published in 1876 by Ahmad Shawal bin Abdul Hamid and Melati Sarawak by Muhammad Rakawi Yusuf in 1927 are among the main resources and grand narratives in the Malay archipelago that will be analyzed regarding the idea of transformation and other aspects such as postcolonialism related in the texts and contexts